A REVIEW ON ANALYTICAL CHALLENGES IN MONITORING AND CONTROLLING GENOTOXIC IMPURITIES - S SUTNGA, VANDAMME; R, RAJESH (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Genotoxic impurities (GIs) are chemical agents that have a DNA-interaction characteristic which can ultimately lead to cancer. Their presence in various drug substances had driven various regulatory authorities to guide monitor, control, and to limit their level in various drug products. The objective of this article is to review the analytical approaches and challenges faced while accessing, monitoring, and controlling GIs in pharmaceuticals and also a brief explanation such as low limits of GIs, matrix interference, non-volatility, and environmental conditions encountered during the analysis of GIs are also discussed in this paper. At present, several modern analytical techniques are being used for the analysis of GIs such as high-performance liquid chromatography, liquid chromatography-mass spectrometry, and gas chromatography-mass spectroscopy that have high selectivity and sensitivity, but at the same time, many researchers have reported several challenges while using these techniques. Impacts of GIs are very important and various international organizations such as the World Health Organization have set out rules for regulating these chemicals. Hence, we can conclude that analytical approaches and their challenges are essential to understand because they play a key role to develop robust analytical methods.